2019
DOI: 10.1016/j.jvs.2018.04.068
|View full text |Cite|
|
Sign up to set email alerts
|

A randomized trial of vonapanitase (PATENCY-1) to promote radiocephalic fistula patency and use for hemodialysis

Abstract: Objective: Arteriovenous fistulas created in patients with chronic kidney disease often lose patency and fail to become usable. This prospective trial evaluated the efficacy of vonapanitase, a recombinant human elastase, in promoting radiocephalic fistula patency and use for hemodialysis. Methods: PATENCY-1 was a double-blind, placebo-controlled trial that enrolled 349 patients on or approaching hemodialysis and being evaluated for radiocephalic arteriovenous fistula creation. Of these, 313 were randomized and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 34 publications
(47 reference statements)
0
33
0
Order By: Relevance
“…Therapeutic manipulation of the small GTPases is particularly attractive for the treatment of surgical diseases. We have the ability to directly treat blood vessels through pressurized perfusion, as in the PREVENT trial [3], or with topical treatment of the target vessel, as in the PATENCY trial [88]. Our group has extensive experience delivering siRNA to isolated vessels and in vivo [14,89,90].…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic manipulation of the small GTPases is particularly attractive for the treatment of surgical diseases. We have the ability to directly treat blood vessels through pressurized perfusion, as in the PREVENT trial [3], or with topical treatment of the target vessel, as in the PATENCY trial [88]. Our group has extensive experience delivering siRNA to isolated vessels and in vivo [14,89,90].…”
Section: Discussionmentioning
confidence: 99%
“…3 Increasing AVF use-a priority of national vascular access recommendations for the past two decades-has been limited by the unexpectedly high rate of AVF maturation failure, ranging from 30% to 60%. [4][5][6][7] Approximately half of new AVFs require one or more interventions to promote their maturation before successful use for dialysis ("assisted maturation"). Two small studies from one to two medical centers reported that AVFs with assisted maturation were associated with more frequent interventions to maintain patency after maturation and had greater AVF abandonment compared with AVFs with unassisted maturation.…”
mentioning
confidence: 99%
“…The 62% successful cannulation rate observed in the LIPMAT study was comparable to previous studies on functional AVF maturation. 1,7 Although the nonsignificant result may be a mere result of a lack of power due to the small sample size, also no trend toward any difference between the treatment and control group was observed. Apart from a lack of statistical power, several factors might explain the lack of therapeutic efficacy of liposomal prednisolone to improve AVF maturation.…”
Section: Discussionmentioning
confidence: 95%